Research Data Management from Hungarian Perspective: A Systematic Literature Review - Galih, Aulia Puspaning; Barát, Ágnes Hajdu (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
In science and education, research data is a valuable resource that can be utilized and repurposed for future use. Research data management is crucial for successful research, as it can generate reliable and advantageous results and facilitate accurate decision-making. The systematic review study followed the PRISMA Statement standards for reporting. Data regarding research data management from a Hungarian perspective was collected from SCOPUS, Web of Science, and EBSCO databases on January 5th, 2024. Forty-one records were identified from SCOPUS, Web of Science, and EBSCO databases. After screening, the remaining 13 articles were included in this study. The Hungarian authors discussed four distinct research data management activities. The activities included data sharing, data citation, data curation, and data storage. Several additional data-related concepts, such as data governance, data quality, data literacy, and research data service, were also examined in this study.